Predictors of tissue healing in ulcerative colitis patients treated with anti-TNF. Issue 1 (January 2017) - Viazis, Nikos; Giakoumis, Marios; Bamias, Giorgos; Goukos, Dimitris; Koukouratos, Theodoros; Katopodi, Konstantina; Karatzas, Pantelis; Triantos, Christos; Tsolias, Chrisostomos; Theocharis, Georgios; Daikos, George L.; Ladas, Spyros D.; et al.
Abstract: Aim: To identify factors predicting mucosal healing in ulcerative colitis patients treated with anti-TNFα agents with or without azathioprine. Methods: In a prospective, multicenter, one-year study biologic naïve patients aged 25–65 years, with corticosteroid-dependent or refractory colitis received combination treatment with anti-TNFα and azathioprine for 6 months followed by anti-TNFα monotherapy. Patients who denied combination therapy or were outside this age range received anti-TNFα monotherapy (controls). Before and at weeks 12 and 54 of treatment the total Mayo score was calculated. Mucosal healing was defined as endoscopic subscore of 0. Mucosal expression of T helper (Th) cell-lineage specific transcription factors (Tbet, Gata3, Rorc, FoxP3) before treatment was also associated with mucosal healing. Results: Of 67 patients, 58 (86.6%) received combination and 9 (13.4%) anti-TNFα monotherapy. Overall 29 (43.3%) patients achieved mucosal healing; rates were higher in patients receiving combination therapy vs. monotherapy (p = 0.03) and in azathioprine naïve vs. exposed patients in the combination group (p = 0.01). Mucosal healing was associated with lower pre-treatment mucosal expression of transcription factor Th1–Tbet (p < 0.05) and higher expression of Th17–Rorc (p < 0.05). Conclusions: Mucosal healing was associated with combination therapy, especially in biologic and azathioprine-naïve patients and pre-treatment mucosal expression of specific Th specific transcripting factors (Tbet and Rorc).